Digital Storytelling in the Era of TikTok and Short-From Video Content - Paramita Hapsari, S.Ds, M.Ds, Paramita Hapsari, S.Ds, M.Ds (Profilm Jurnal Ilmiah Ilmu Perfilman dan Pertelevisian, 2024)
The research investigates how platforms like TikTok can change the way stories are told in short videos and how that impacts digital videography production methods. Additionally, the study investigates how TikTok's recommendation algorithm affects the distribution and visibility of digital content and their influence on content diversity and inclusion. This study utilizes both qualitative and quantitative approaches. The study looks at the different approaches used by content creators on TikTok, as well as how the platform's algorithm selects and displays content to users. Research shows that TikTok's algorithm driven by user engagement personalizes the viewing experience by displaying content that suits individual preferences. This increases user engagement but also creates "filter bubbles" that can limit exposure to different types of content. In addition, these algorithms usually support already popular content, which allows videos to go viral quickly, but they prefer to support content that is already popular, which is difficult for new creators or niche content to get attention from. This research resulted in the discovery that Tik Tok's algorithm can help creator diversity by providing a platform for underrepresented voices. However, these algorithms have a risk of bias that can affect the visibility of content based on geographic location and demographics. This can lead to some groups of creators not being well represented or accepted. Case studies such as LGBTQ+ creator "BlackLivesMatter" and viral phenomenon "Ratatouille Musical" show that TikTok's algorithm has the ability to encourage creative cooperation and social movements, although initially the success of content depends on the ability to get engagement from its users. Additionally, the study found that TikTok's algorithm has a significant influence on the platform's diversity and inclusion, as well as the visibility and distribution of storytelling digital content. Therefore, it is important to understand and address algorithmic bias to ensure that everyone views TikTok correctly and inclusively.